An Improved Clustering Algorithm Using Fuzzy Relation for the Performance Evaluation of Humanistic Systems. Issue 12 (18th October 2014) - Beg, Ismat; Rashid, Tabasam
<x xml:space="preserve">Abstract</x> A hierarchical structure is proposed for the performance evaluation of vague, complicated humanistic systems. An improved fuzzy clustering algorithm is developed to produce several partition trees with different levels and clusters according to different triangular norm compositions. Additionally, a fuzzy clustering algorithm is given to produce a partition tree without using the transitive closure composition. The usefulness of the proposed algorithm is illustrated by an example of actual academic data.